Retrosternal esophagocoloplasty with transverse isoperistaltic: Time before radical esophagectomy or exclusively antidysphageal method. Experience on 15 cases. - Gómez Gotuzzo, Francisco (Cirugía del Uruguay, 1975)
15 patients with esophageal cancer (a lmost al1 of oí thp. rnlddle third), without prcvious selecUOI:, were treaed by rctrosternal coloplastia wlth isoperistaltic tnms....erse colon. Four of them, who we cO lsldered resectable, were submitted to secondary esophagectomy 4 weeks later. Slx out 01 the total died within one m!lnth arter operation, 5 01 tht!m due to direct complicatlons oí surge:ry; the othcr nine !lurvived from 4 to 19 months without recurrence of the dysphagia. The value ol the procedure as a palliative is remarked, for It considerably improves the Quallty ol lhe survivaL